Associations of multiple lipoprotein and apolipoprotein measures with worsening of glycemia and incident type 2 diabetes in 6607 non-diabetic Finnish men. Issue 1 (May 2015) - Fizelova, Maria; Miilunpohja, Manna; Kangas, Antti J.; Soininen, Pasi; Kuusisto, Johanna; Ala-Korpela, Mika; Laakso, Markku; Stančáková, Alena
Abstract Objective We investigated the association of various lipoprotein traits, apolipoproteins and their ratios with the deterioration of glycemia, incident type 2 diabetes, insulin resistance and insulin secretion in a large population-based Metabolic Syndrome Men (METSIM) Study. Research design and methods The METSIM Study includes 10, 197 Finnish men, aged 45–73 years, and examined in 2005–2010. From 6607 non-diabetic participants without statin treatment at baseline, 386 developed incident type 2 diabetes during a 5.9-year follow-up. A total of 3330 non-diabetic participants without statin treatment had both baseline and follow-up visit data, and were included in statistical analyses of the worsening of glycemia. Results Compared to single lipid and lipoprotein measurements, lipoprotein and apolipoprotein ratios were better predictors of the glucose area under the curve and incident type 2 diabetes after adjustment for confounding factors. The apolipoprotein B/LDL cholesterol ratio was the strongest predictor of the worsening of glycemia, whereas the apolipoprotein A1/HDL cholesterol ratio was the strongest predictor of incident type 2 diabetes. The associations of lipoprotein traits, apolipoproteins and their ratios with insulin sensitivity were stronger than those with insulin secretion. Conclusions The apolipoprotein B/LDL cholesterol and apolipoprotein A1/HDL cholesterol ratios were the strongest predictors of the worsening of glycemia and incident type 2 diabetes, respectively.